Enhanced stability and performance of inverted perovskite solar cell using titanium interlayer. Issue 1 (July 2021) - Sun, Tian; Lin, Xiaoyun; Wang, Ya; Zhong, Hong; Zhou, Hang
Abstract: Metal atom diffusing in perovskite solar cells (PSCs) results in pernicious effects, leading to degradation of efficiency and long-term stability. Here we report the potential of titanium (Ti) acting as permeation barrier interlayer between organic layer and metal electrode. The thin, compact titanium layer not only insulates active layer from external moisture, but also keeps metal electrode from further corrosion. By introducing titanium interlayer, open circuit voltage (Voc ) and fill factors (FF) are both enhanced, presenting a power conversion efficiency of 20.52% (Voc of 1.127 V, Jsc of 22.136 mA/cm 2, FF of 82.299%). Furthermore, the unencapsulated devices maintain 98.3% of their initial efficiency after 85°C thermal aging in ambient atmosphere (air, Relative Humidity: 50%-60%) for 55 hours.